2019
DOI: 10.1074/mcp.tir118.000918
|View full text |Cite
|
Sign up to set email alerts
|

Precision De Novo Peptide Sequencing Using Mirror Proteases of Ac-LysargiNase and Trypsin for Large-scale Proteomics

Abstract: The developed acetylated LysargiNase (Ac-LysargiNase), with superior activity and stability, provides complementary ion types compared with trypsin for MS/MS analysis. Based on the two mirror proteases, we developed a novel de novo sequencing algorithm, pNovoM, which performed with higher efficiency and accuracy compared with other software tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Gaps in the b and y ion series of the trypsin spectra can be filled in using the Ac‐LysargiNase spectra and vice versa which results in fuller coverage of the peptide. The authors of this method 42 found that in a test set of Escherichia coli proteome samples around 50% of the peptides had both trypsin and Ac‐LysargiNase spectra, and the mirror spectra were able to reach 97% coverage of either the y or b ion series 42 . They created the software tool pNovoM to pair mirror spectra and perform the de novo search.…”
Section: Data Acquisition and Sample Preparation Methods For Improvinmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaps in the b and y ion series of the trypsin spectra can be filled in using the Ac‐LysargiNase spectra and vice versa which results in fuller coverage of the peptide. The authors of this method 42 found that in a test set of Escherichia coli proteome samples around 50% of the peptides had both trypsin and Ac‐LysargiNase spectra, and the mirror spectra were able to reach 97% coverage of either the y or b ion series 42 . They created the software tool pNovoM to pair mirror spectra and perform the de novo search.…”
Section: Data Acquisition and Sample Preparation Methods For Improvinmentioning
confidence: 99%
“…40 Yang et al have shown how using complementary enzymes can produce what they call mirror spectra. 42 Mirror spectra can be produced by digesting the sample (in parallel reactions) with trypsin (which cuts the peptide bond C-terminal to lysine and arginine residues) and LysargiNase (which cuts on the N-terminal side of lysine and arginine residues). This results in paired sets of peptides that differ only by having a basic residue at the Nor the C-terminus, called mirror peptides.…”
Section: Distinguishing Fragment Ion Typesmentioning
confidence: 99%
“…Furthermore, precise de novo peptide sequencing is hindered by poor coverage of b and/or y ion series, which is a common problem in SUMOylation identification by MS. Recently, a protein digestive enzyme Ac‐LysargiNase has been reported to provide a better coverage and stronger signal of b ions compared to tryptic peptides , it also can work with trypsin to create a complementary ion series. So, the application of Ac‐LysargiNase in SUMOylation identification is also a technical improvement.…”
Section: Perspectivesmentioning
confidence: 99%
“…A large variety of informatics tools have been developed to aid in assay development and to process the data collected by various acquisition types [14,15]. Novel bioinformatics tools include quality control algorithms [16], de novo peptide sequencing [17], and webbased resources for dissemination of results [18].…”
Section: Introductionmentioning
confidence: 99%